PTEN Germline Mutations in Patients Initially Tested for Other Hereditary Cancer Syndromes: Would Use of Risk Assessment Tools Reduce Genetic Testing?. (13th September 2013) - Mester, Jessica L.; Moore, Rebekah A.; Eng, Charis
Learning Objectives: Cite the risk assessment tools available for several hereditary cancer predisposition syndromes. Describe ways in which use of these risk assessment tools can lead to cost savings and decreased time to correct diagnosis. Explain the impact of correct genetic diagnosis on the patient's medical management and on predictive testing for family members. Abstract : Purpose: PTEN Hamartoma Tumor syndrome (PHTS) includes patients with Cowden syndrome or other syndromes with germline mutation of the PTEN tumor suppressor gene. The risk for breast, colorectal, and endometrial cancer and polyposis is increased, creating clinical overlap with hereditary breast and ovarian cancer (HBOC), Lynch syndrome (LS), and adenomatous polyposis syndromes (APS). We reviewed our series of patients with PHTS to determine how often testing criteria for these syndromes were met and how often other‐gene testing was ordered before testing PTEN . Patients and Methods: Patients were prospectively recruited by relaxed International Cowden Consortium criteria or presence of known germline PTEN mutation. Mutations were identified by mutation scanning/multiplex ligation‐dependent probe amplification analysis and confirmed by sequencing/quantitative polymerase chain reaction. Patients were excluded if they were adopted, were <18 years of age, or if they were diagnosed with Cowden syndrome before 1998. Standard risk‐assessment models were applied to determine whether patients met HBOC testing criteria, LS‐relevant Amsterdam II/Bethesda 2004 criteria, or had adenomatous polyps. Prior probability of PTEN mutation was estimated with the Cleveland Clinic PTEN risk calculator. Results: Of 137 PTEN mutation‐positive adult probands, 59 (43.1%) met testing criteria for HBOC or LS. Of these, 45 (32.8%) were first offered HBOC, LS, or APS testing. Of those who underwent APS testing, none of the six patients met criteria. Initial risk assessment by a genetics specialist was significantly associated with immediate PTEN testing in patients also meeting HBOC testing criteria. Using this PTEN risk assessment tool could have spared gene testing for 22 unlikely syndromes, at a total cost of $66, 080. Conclusion: PHTS is an important differential diagnosis for patients referred for HBOC, LS, or APS. Risk assessment tools may help focus genetic analysis and aid in the interpretation of multiplex testing. Abstract : PTEN Hamartoma Tumor syndrome (PHTS) is a hereditary condition causing increased risk for neoplasia types seen in persons with Hereditary Breast and Ovarian Cancer, Lynch, and Adenomatous Polyposis syndromes. We reviewed our series of patients with PHTS to determine how often testing criteria for these syndromes were met and how often other‐gene testing was ordered before testing PTEN .